2000
DOI: 10.1063/1.126574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain transfer on critical thickness for epitaxial layers grown on compliant substrate

Abstract: Articles you may be interested inMechanisms of edge-dislocation formation in strained films of zinc blende and diamond cubic semiconductors epitaxially grown on (001)-oriented substrates Critical thickness of a heteroepitaxial film on a twist-bonded compliant substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…As for cylindrical composite systems, in plate-like composites the critical film thickness increases with a decrease in substrate thickness [43][44][45]. The reduction of the critical thickness of a plate-like film with substrate thickness is due to the elastic deformation of the substrate, which partially accommodates the misfit-induced elastic strains in the film (e.g., see [46][47][48][49][50][51] Plate-like and cylindrical film/substrate systems are also similar in that for both the systems, misfit dislocation generation conditions may be presented in terms of the critical misfit eigenstrain (denoted by f m for a cylindrical system and by f 0 m for a plate-like one) or critical substrate thickness (denoted respectively by R 0c and H s c ). The plot of the relation between these two critical parameters provides an upper bound for the region of misfit eigenstrains and substrate thicknesses in which misfit dislocations cannot be generated at any film thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for cylindrical composite systems, in plate-like composites the critical film thickness increases with a decrease in substrate thickness [43][44][45]. The reduction of the critical thickness of a plate-like film with substrate thickness is due to the elastic deformation of the substrate, which partially accommodates the misfit-induced elastic strains in the film (e.g., see [46][47][48][49][50][51] Plate-like and cylindrical film/substrate systems are also similar in that for both the systems, misfit dislocation generation conditions may be presented in terms of the critical misfit eigenstrain (denoted by f m for a cylindrical system and by f 0 m for a plate-like one) or critical substrate thickness (denoted respectively by R 0c and H s c ). The plot of the relation between these two critical parameters provides an upper bound for the region of misfit eigenstrains and substrate thicknesses in which misfit dislocations cannot be generated at any film thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of the critical parameter f 0 m (such that at jf j < f 0 m MDs cannot be formed at any film thickness) for a plate-like one follows from the existence of the critical value H s c ðf Þ [45] of the substrate thickness H s , which coincides with the critical film thickness [52] for a semi-infinite-substrate/film system. The critical condition H s < H s c ðf Þ (for the absence of MDs at any film thickness) can also be presented in terms of the critical misfit eigenstrain f 0 m (jf j < f 0 m ðH s Þ) which decreases as H s increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research over the past 15 years [10,15,18,20,21,24,29] has identified various methods to understand the mechanical behavior of compliant substrates. In addition, methods to assess the substrate/film interface stability have also been considered [14,29].…”
mentioning
confidence: 99%
“…In addition, methods to assess the substrate/film interface stability have also been considered [14,29]. These methods include molecular dynamics [12] and continuum mechanics [5, 10,11,14,15,18,20,21,24,29]. Other studies on the mechanisms of deformation at the nanoscale have included a combination of molecular simulations and continuum analyses [1].…”
mentioning
confidence: 99%